Unraveling Main Limiting Sites of Photosynthesis under Below- and Above-Ground Heat Stress in Cucumber and the Alleviatory Role of Luffa Rootstock - Li, Hao; Ahammed, Golam J.; Zhou, Guona; Xia, Xiaojian; Zhou, Jie; Shi, Kai; Yu, Jingquan; Zhou, Yanhong (Frontiers in Plant Science, 2016)
Photosynthesis is one of the most thermo-sensitive processes in plants. Although the severity of heat stress could be attenuated by grafting approach, the primary damaged site of photosynthesis system under heat stress and the regulatory mechanism of rootstock-mediated heat tolerance are poorly understood. In the current study, cucumber plants grafted onto their own roots and heat-tolerant luffa roots were exposed to root-zone heat (25/40 °C) and aerial heat (40/25 °C) individually and in combination (40/40 °C) to understand the response of photosynthetic process by investigating energy absorption and distribution, electron transport in photosystem (PS) II and I, and CO2 assimilation. According to the results, root-zone heat stress inhibited photosynthesis mainly through decreasing Rubisco activity, while aerial heat stress mainly through inhibiting PSII acceptor side. The imbalance in light absorption and utilization resulted in accumulation of reactive oxygen species that caused damage to photosynthetic apparatus, forming a vicious cycle. On the contrary, grafting cucumber onto heat-tolerant luffa rootstock alleviated heat-induced photosynthetic inhibition and oxidative stress by maintaining higher root vitality, HSP70 accumulation, and antioxidant potential.